Chemical Compounds of Coffee Ground and Spent Coffee Ground for Pharmaceutical Products - Anton Restu Prihadi; Askal Maimulyanti (UIN Syarif Hidayatullah Jakarta, 2021)
Coffee is one of the most valuable primary products in world trade. Coffee production generates a lot of coffee waste such as spent coffee grounds. The chemical components of the coffee ground and spent coffee ground were caffeine and chlorogenic acid. These components were important to apply in pharmaceuticals. This research conducted the identification of functional groups of coffee grounds and spent coffee grounds and analysis of the active compounds of caffeine and chlorogenic acid in the sample. Both samples have the same infrared spectrum and contain the main functional groups O-H, C-N, and C-H. The active substances in the spent coffee grounds were found to be caffeine 0.35% and chlorogenic acid 0.16%, while in coffee ground coffee before brewing it was obtained 1.41% caffeine and 1.50% chlorogenic acid. The waste of spent coffee grounds has a potential component and it can be used in pharmaceuticals.